Example-Driven Program Synthesis for End-User Programming. (Communications of the ACM, 2012)
An introduction is presented in which the author discusses the computer research article "Spreadsheet Data Manipulation Using Examples," by Sumit Gulwani, William R. Harris, and Rishabh Singh.